Warm-up exercises may not be so important for enhancing submaximal running performance - Takizawa, K.; Yamaguchi, T.; Shibata, K. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this study was to determine an appropriate warm-up intensity for enhancing performance in submaximal running at 90% vVO2max (it assumes 3,000-5,000 m in track events). Seven trained male university athletes took part in this study (age: 21.3 ± 2.1 years, height: 169.3 ± 4.7 cm, body mass: 58.4 ± 5.6 kg, VO2max: 73.33 ± 5.46 ml/kg/min). Each subject ran on a treadmill at 90% vVO2max until exhaustion after 1 of 4 warm-up treatments. The 4 warm-up treatments were no warm-up, 15 minutes running at 60% vVO2max, at 70% vVO2max, and at 80% vVO2max. The running performance was evaluated by time to exhaustion (TTE). VO2, and vastus lateralis muscle temperature were also measured. There were no significant differences in TTE among the warm-up exercises (p > 0.05). VO2 in no warm-up showed slower reaction than the other warm-up exercises. Regarding, the vastus lateralis muscle temperature immediately after warm-up, no warm-up was significantly (p < 0.01) lower compared with the other warm-up exercises. Our results suggested that submaximal running performance was not affected by the presence or absence of a warm-up or by warm-up intensity, although physiological changes occurred.